Democratic Theory's Evasion of Race. Issue 2 (12th August 2021) - Hytten, Kathy; Stemhagen, Kurt
Abstract: In this essay, Kathy Hytten and Kurt Stemhagen explore the evasion of race, particularly implicit whiteness, in democratic theory. The authors maintain that democratic theorists, especially those who write about education, avoid discussions of race, often writing in universal terms about democracy while ignoring the ways that ostensibly democratic societies reproduce white supremacy. Hytten and Stemhagen begin by describing critiques of the whiteness of democracy; next, they draw on three different approaches to democracy — decolonial, abolitionist, and Black pragmatist — to explore how we can work to disentangle the workings of democracy from racism. Significantly, all of the approaches they address center the voices of scholars of color and each one provides specific charges, resources, and tools for doing democracy differently and in ways that are explicitly antiracist.